Current and future burden of gynecological cancers attributable to high body-mass index: A comprehensive global analysis and projection study - Xuanyu Zhao; Weimin Kong; Yan Jiang; Feng Sui (PLoS ONE, 2025)
Background High body-mass index (BMI) is a major modifiable risk factor for gynecological cancers, yet its contribution to the global cancer burden remains incompletely characterized. This study provides a comprehensive analysis of the current burden of gynecological cancers attributable to high BMI and projects future trends through 2050. Methods We analyzed data from the Global Burden of Disease (GBD) 2021 study, examining uterine and ovarian cancers attributable to high BMI across 204 countries and territories. Burden was quantified using deaths and disability-adjusted life years (DALYs). Temporal trends were identified using joinpoint regression analysis, while future burden was projected using Bayesian Age-Period-Cohort (BAPC) models. We evaluated relationships between socio-demographic index (SDI) and cancer burden to identify development-associated patterns. Results Between 1990 and 2021, global deaths from gynecological cancers attributable to high BMI increased by 143.4% (from 20,743–50,479), with corresponding DALYs rising by 141.7% (from 561,515–1,357,395). Rising age-standardized rates indicated increasing individual-level risk. While burden was highest in high-SDI regions, the most rapid increases occurred in low- and middle-SDI settings. Cancer-specific patterns varied, with uterine cancer showing consistent increases across all SDI quintiles, while ovarian cancer exhibited decreasing trends in high-SDI regions after 2003. Projections indicate a 2.6-fold increase in deaths by 2050, with differential growth by cancer type: a 3.2-fold increase for ovarian cancer versus 2.3-fold for uterine cancer. Conclusions The global burden of gynecological cancers attributable to high BMI has increased substantially and is projected to accelerate through 2050, particularly in developing regions. These findings underscore the urgent need for targeted obesity prevention strategies within comprehensive cancer control programs to avert a substantial proportion of future gynecological cancer cases.